Why regions fail (or succeed). The Role of Government Institutions in the Long-Run - Filippo Bonanno (European Journal of Government and Economics (EJGE), 2019)
This paper represents an attempt to reconcile some general intuitions provided by Daron Acemoglu and James A. Robinson in the book "Why Nations Fail" with the case of the deep regional disparities in the economic performances observed within the "Western" European Union during the period 2001-2015. By adopting an approach to growth analysis based on binary response models, this paper quantifies the extent to which the quality of government institutions has shaped regional economic performances in the European Union throughout the period comprising the Great Recession. Empirical results show that: 1) The higher is the quality of institutions, the higher is the probability that a region with high income per capita will grow above the levels of the European Union as a whole. 2) The higher is the quality of institutions, the lower is the probability that a low-income region will grow below the levels of European Union as a whole. 3) The higher is the quality of institutions, the higher (lower) is the probability that any region, regardless of its income per capita, will outperform (underperform) the European Union as a whole. 4) The higher is the quality of Institutions, the lower is the probability that a region will "fail" to grow.
Keywords: H01; N04; R01; C10; 330; quality of institutions; European Union; economic performances; probit